2015
DOI: 10.1016/j.jagp.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Cognitive Complaints, Personality and Brain Amyloid-beta in Cognitively Normal Older Adults

Abstract: Objectives Subjective cognitive complaints in otherwise normal aging are common but may be associated with preclinical Alzheimer Disease in some individuals. Little is known about who is mostly likely to show associations between cognitive complaints and preclinical Alzheimer pathology. We sought to 1) demonstrate associations between subjective complaints and brain amyloid-β in cognitively normal older adults; 2) to explore personality factors as potential moderators of this association. Design Cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
87
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 60 publications
7
87
1
4
Order By: Relevance
“…It is not uncommon to observe anxiety and depresive symptoms among SCD particpants. In fact, self reported measures of SCD correlate more with personality traits than with AD biomarkers, being the opposite with proxy-related questionnaires (61, 90). Neverthelees, patients at early stages of AD also present emotional, psychological and mild behavioral disturances (113).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…It is not uncommon to observe anxiety and depresive symptoms among SCD particpants. In fact, self reported measures of SCD correlate more with personality traits than with AD biomarkers, being the opposite with proxy-related questionnaires (61, 90). Neverthelees, patients at early stages of AD also present emotional, psychological and mild behavioral disturances (113).…”
Section: Discussionmentioning
confidence: 84%
“…These studies, however, should make their aims clear and distinguish their approach from the study of SCD in preclinical AD. The majority of SCD studies will focus on early AD identification and prediction of cognitive decline and dementia or will aim to identify subjects in the preclinical stage of AD for intervention trials (2, 8, 16, 26, 61). These studies will treat a major psychiatric diagnosis as an exclusion criterion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas most studies have reported an association between SMCs and Ab, [3][4][5][6] others could not demonstrate this relationship. 7 Previous studies with fluorodeoxyglucose (FDG)-PET, a biomarker supposed to reflect neuronal integrity, 8 have demonstrated hypometabolism when comparing cognitively normal (CN) individuals with and without SMCs, but the results have been inconsistent as to which brain regions show hypometabolism, e.g., the precuneus, 9 parietotemporal and parahippocampal gyrus, 10 or periventricular region.…”
mentioning
confidence: 97%